Protective role for kidney TREM2 macrophages in obesity- and diabetes-induced kidney injury - Ayshwarya Subramanian; Katherine A. Vernon; Yiming Zhou; Jamie L. Marshall; Maria Alimova; Carlos Arevalo; Fan Zhang; Michal Slyper; Julia Waldman; Mónica S. Montesinos; Danielle Dionne; Lan Nguyễn; et al. (2024)
Diabetic kidney disease (DKD), the most common cause of kidney failure, is a frequent complication of diabetes and obesity, and yet to date, treatments to halt its progression are lacking. We analyze kidney single-cell transcriptomic profiles from DKD patients and two DKD mouse models at multiple time points along disease progression—high-fat diet (HFD)-fed mice aged to 90–100 weeks and BTBR ob/ob mice (a genetic model)—and report an expanding population of macrophages with high expression of triggering receptor expressed on myeloid cells 2 (TREM2) in HFD-fed mice. TREM2high macrophages are enriched in obese and diabetic patients, in contrast to hypertensive patients or healthy controls in an independent validation cohort. Trem2 knockout mice on an HFD have worsening kidney filter damage and increased tubular epithelial cell injury, all signs of worsening DKD. Together, our studies suggest that strategies to enhance kidney TREM2high macrophages may provide therapeutic benefits for DKD.